(untitled) (CIPEEX, 2022)
WITH THE BEGINNING OF A SIMPLIFIED WRITTINGFROM THE SUMERIAN PEOPLE, AROUND3.500 B.C. HUMANKIND STARTED BEING ABLE TO STORAGE AND REGISTER ITS OWN LAWS, CULTURE AND HISTORY IN CLAY BRICKS AND AFTERWARDS, SCROOLS.WITH THE ARRIVAL OF THE TECHNICALSCIENTIFIC-INFORMATIONAL REVOLUTION, AROUND THE XX CENTURY, THE WAY INFORMATION WAS KEPT CHANGED, SWITCHING FROM PHYSICAL RECODS TO DIGITAL ONES.THIS WORK HAS THE OBJECTIVE OF DEVELOPING A PLATFORM UNTIL THE END OF THE COURSE, HAVING THE FUNCTIONALITY OF HELPING INSTITUTIONAL MANAGEMENT, BEING PUBLIC OR PRIVATES. IT IS WORTH TO POINT THAT THE MANAGEMENT OF EDUCATIONAL ORGANIZATIONS WILL HAPPEN THROUGH MODULES FOR THAT ESPECIFIC REA, FOR EXAMPLE, MODULES FOR SIGNING UP, RELEASE/ANALYSIS OF SCORES AND FREQUENCY, RESERVING/ ANALYSIS OF PHYSICAL SPACES, EVENT CONTROLS, AND OTHERS. THE PRIORITY FOR PROJECT PROTOTYPE DEVELOPMENT WILL UTILIZE A FEW TECHNOLOGIES, FOR EXAMPLE, JAVASCRIPT AND DJANGO LIBRARIES ASIDE FROM PYTHON FRAMEWORK. HAVING OBJECT ORIENTATION AS PROGRAMMING AND DATA BANK PARADIGMS. AS RESULTS, IT IS EXPECTED A PLATFORM THAT IS INTUITIVE, RESPONSIVE, ESTABLE AND SECURE